Activation of the Cholinergic Anti-inflammatory Pathway Attenuated Angiotension II-Dependent Hypertension and Renal Injury - Wu, Shu-jie; Shi, Zhe-wei; Wang, Xue; Ren, Fang-fang; Xie, Zuo-yi; Lei, Li; Chen, Peng (Frontiers in Pharmacology, 2021)
Background—Angiotensin II (AngII) induces renal fibrosis, characterized by fibroblast proliferation, inflammatory cell infiltration and excessive extracellular matrix deposition, all of which lead to hypertension. The vagus nerve-related cholinergic anti-inflammatory pathway (CAP) modulates local and systemic inflammatory responses. The aim of present study was to determine the effect of CAP on renal inflammation and fibrosis. Methods and results—AngII-induced hypertension was induced in vivo by 14-day low-dose AngII infusion from osmotic minipumps. We used GTS-21 dihydrochloride, a selective nicotinic acetylcholine receptor agonist. Daily intraperitoneal GTS-21 injection and/or vagotomy started after hypertension was confirmed and continued for 4 weeks. The elevated blood pressure caused by AngII was significantly attenuated by GTS-21. Improved baroreflex sensitivity was observed after GTS-21 administration. Masson stain and immunoblotting revealed that deposition of excessive fibrosis and overexpression of inflammatory cytokines induced by AngII was reduced by GTS-21. To determine the role of autonomic control in CAP, unilateral vagotomy was performed. Vagotomy weakened the effect of CAP on AngII-induced hypertension. In vitro, GTS-21 suppressed NF-κB activation, attenuated AngII-induced epithelial–mesenchymal transition and reduced inflammation and fibrosis in NRK-52E cells; α-bungarotoxin (an α7-nAChR selective antagonist) partly inhibited these effects. Conclusion—CAP protected against AngII-induced hypertension via improvement in autonomic control, suppression of NF-κB activation, and reduction of renal inflammation and fibrosis.